2011
DOI: 10.1538/expanim.60.481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Types of Mixed Anesthetic Agents Alternate to Ketamine in Mice

Abstract: Ketamine is usually used for murine anesthesia in animal experiments with other anesthetics for its sedation and analgesic effects. However, ketamine was categorized as a narcotic drug in Japan on January 1, 2007. After this act came into effect, a narcotic handling license became necessary for using and possessing ketamine. Pentobarbital sodium, which is also used for laboratory animal experiments as Nembutal, is no longer being manufactured. For these reasons, other anesthetic agents that can be used without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
337
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(359 citation statements)
references
References 23 publications
3
337
0
Order By: Relevance
“…The lowest HR was observed with medetomidine and xylazine, similar to that reported by Redfors et al (2014) who, using the ketamine/xylazine combination (30/5 mg/kg), observed a HR even lower than seen in our study with the same anaesthetic combination but at a higher concentration (75/5 mg/kg). It has been reported that the effect of combinations of ketamine and xylazine depends on the quantities of ketamine and xylazine (Arras et al 2001;Kawai et al 2011). The other combinations produced a small reduction in HR (Arras et al 2001;Orr et al 2005), with a lower reduction in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest HR was observed with medetomidine and xylazine, similar to that reported by Redfors et al (2014) who, using the ketamine/xylazine combination (30/5 mg/kg), observed a HR even lower than seen in our study with the same anaesthetic combination but at a higher concentration (75/5 mg/kg). It has been reported that the effect of combinations of ketamine and xylazine depends on the quantities of ketamine and xylazine (Arras et al 2001;Kawai et al 2011). The other combinations produced a small reduction in HR (Arras et al 2001;Orr et al 2005), with a lower reduction in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…administration, relative safety among injectable agents, and ability to produce CNS effects such as catalepsia, analgesia, dissociation from environment and amnesia (Murray et al 2000;Richardson and Flecknell 2005;Baker et al 2011;Kawai et al 2011). Plumb (2008 indicates a dose of 50-100 mg/kg of ketamine only in mice.…”
Section: Discussionmentioning
confidence: 99%
“…After an acclimation period of 1 week, the mice were subjected to bilateral ovariectomy (OVX) or a sham operation via a dorsolateral incision after intraperitoneal administration of a combination anaesthetic [medetomidine hydrochloride, 0.3 mg/kg (Domitol; Nippon Zenyaku Kogyo Co., Ltd., Fukushima, Japan); midazolam, 4.0 mg/kg (Sandoz; Sandoz K.K. Tokyo, Japan) and butorphanol, 5.0 mg/kg (Vetorphale; Meiji Seika Pharma Co., Ltd., Tokyo, Japan)] (20,21). For OVX, the ovaries were excised, oviducts were put back in their original position and the incisions were closed.…”
Section: Methodsmentioning
confidence: 99%